Financial fraud in developing countries: Common scam detection tips do not help distinguish scam from non-scam messages - Elif Kubilay; Eva Raiber; Lisa Spantig; Jana Cahlíková; Lucy Kaaria (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
The expansion of digital financial services raises serious consumer protection concerns, including fraud, especially in developing countries. This column reports findings from an online experiment in Kenya which suggest that conventional scam detection tips do not improve individuals' ability to distinguish between scams and genuine messages. Rather, they make people over-cautious - a result partly driven by official communication often including scam markers.
Keywords: 330